Mining and Analysis of Production Characteristics Data of Tight Gas Reservoirs - Liu, Baolei; Li, Changxuan (Processes, 2023)
The production characteristics of gas reservoirs are one of the important research subjects in gas reservoir development. To better guide the production development and strategy formulation of tight gas reservoirs, it is necessary to utilize data mining techniques to clarify the production characteristics of different reserves types of tight gas reservoirs. The production varies with the size of the recoverable reserves. In this study, 261 tight gas reservoirs worldwide were divided into three categories based on the size of their recoverable reserves. By considering the complete lifecycle of tight gas reservoirs, the production variations were classified into 16 production features, and these features were compiled into a dataset. Three algorithms, namely random forest, LightGBM, and CatBoost, were trained separately to analyze the relationship between the production characteristics and the size of the recoverable reserves of tight gas reservoirs. The objective was to define the production characteristics of tight gas reservoirs with different reserve sizes. Consequently, a set of production characteristic judgment rules that align with the size of the recoverable reserves of tight gas reservoirs was established. The findings revealed that LightGBM provided accurate predictions for the development characteristics of tight gas reservoirs with different reserve sizes. The production characteristics of large-scale tight gas reservoirs are as follows: the cumulative production at the end of the production increase phase ranges from 10 to 115.8 billion cubic meters, while the cumulative production at the end of the stable production phase ranges from 7.9 to 154.9 billion cubic meters. The peak production ranges from 2.3 to 3.8 billion cubic meters, and the decline period is estimated to last between 40 to 51 years. For medium-scale tight gas reservoirs, the production characteristics are as follows: the cumulative production at the end of the production increase phase ranges from 2.5 to 10 billion cubic meters, while the cumulative production at the end of the stable production phase ranges from 2.4 to 7.9 billion cubic meters. The peak production ranges from 0.8 to 2.3 billion cubic meters, and the decline period ranges from 20 to 40 years. As for small-scale tight gas reservoirs, the production characteristics are as follows: the cumulative production at the end of the production increase phase ranges from 0.1 to 2.5 billion cubic meters, while the cumulative production at the end of the stable production phase ranges from 0.2 to 2.4 billion cubic meters. The peak production ranges from 0.005 to 0.8 billion cubic meters, and the decline period ranges from 3 to 20 years. This study can provide potential references for the formulation of development technology policies for tight gas reservoirs and the assessment of reservoir production potential.